2020
DOI: 10.1021/acsmedchemlett.0c00193
|View full text |Cite
|
Sign up to set email alerts
|

Remodelin Is a Cryptic Assay Interference Chemotype That Does Not Inhibit NAT10-Dependent Cytidine Acetylation

Abstract: Remodelin is a putative small molecule inhibitor of the RNA acetyltransferase NAT10 which has shown preclinical efficacy in models of the premature aging disease Hutchinson− Gilford Progeria Syndrome (HGPS). Here we evaluate remodelin's assay interference characteristics and effects on NAT10-catalyzed RNA cytidine acetylation. We find the remodelin chemotype constitutes a cryptic assay interference compound, which does not react with small molecule thiols but demonstrates protein reactivity in ALARM NMR and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In line with this prediction, Larrieu et al reported decreased acetyltransferase activity upon treatment with Remodelin in an in vitro study conducted in Hutchinson-Gilford progeria syndrome (HGPS) 7 . A biophysical study by Shrimp et al 2020 showed that Remodelin does not inhibit NAT10 dependent cytidine acetylation and could interact with multiple protein targets in the cell 21 . Contrary to this assertion, our predictive study is in line with Larrieu et al showing Remodelin binds to the acetyl-CoA binding site, and could affect acetylation activity by preventing the proper binding of acetyl-CoA which is a substrate to RNA and protein acetylation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with this prediction, Larrieu et al reported decreased acetyltransferase activity upon treatment with Remodelin in an in vitro study conducted in Hutchinson-Gilford progeria syndrome (HGPS) 7 . A biophysical study by Shrimp et al 2020 showed that Remodelin does not inhibit NAT10 dependent cytidine acetylation and could interact with multiple protein targets in the cell 21 . Contrary to this assertion, our predictive study is in line with Larrieu et al showing Remodelin binds to the acetyl-CoA binding site, and could affect acetylation activity by preventing the proper binding of acetyl-CoA which is a substrate to RNA and protein acetylation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported Remodelin as a potential cancer drug therapeutic agent, 43,44 but its structural NAT10 binding information is not yet available. 45,46 After sufficient overexpression of NAT10 in mouse hearts, Remodelin failed to show its preventive effects after TAC challenge, indicating that Remodelin acts by inhibiting NAT10 (Figure S10F). Therefore, our findings suggest that Remodelin holds potential as a viable therapeutic intervention for the prevention and treatment of cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the effort for pharmaceutically targeting NAT10‐ac4C should not be abandoned; especially there are already some highly specific NAT10 binding molecules available. Although their efficacy for acetyltransferase activity inhibition seems to be weak 7,8 . Learn from the success of small molecular inhibitor development for m6A modification, 9 investigators are expected to develop potent molecule for NAT10‐ac4C inhibition in a foreseeable future.…”
Section: Figurementioning
confidence: 99%
“…Although their efficacy for acetyltransferase activity inhibition seems to be weak. 7,8 Learn from the success of small molecular inhibitor development for m6A modification, 9 investigators are expected to develop potent molecule for NAT10-ac4C inhibition in a foreseeable future.…”
mentioning
confidence: 99%